Adaptation and Initial validation of student stress inventory in Malay sample - Abdul Kudus, Farah Nadiah; Shamsul, Nur Syazera; Abdul Rahman, Shukran (IIUM Press, International Islamic University Malaysia, 2020)
The paper discusses the process to adapt the Student Stress Inventory (SSI) and reportsthefindingofitscontentvalidation. Theprocessentailed,firstly,forwardand backward translation of items to be used in a new population of test takers whose culture is different from that of in the original SSI standardization sample. The translation process was accomplished by subject matter experts (SMEs) who are well- versed in the English and Malay languages. They too understand the nature and extent of culture in the destination and original culture. The second stage was the item verification process in which five SMEs (Clinical Psychologist, Counsellor, Linguist, English teacher and Parent) verified and provided comments on every item before subjecting them to content and face validation stage. 10 SMEs, who were Psychology graduates, have been engaged to judge if the adapted Malay items are essential in measuring the construct-in-question among the Malay test takers. The SME judgments were calculated to obtain the content-validity-ratio (CVR) of each item. Items which did not meet the minimum value of CVR have been further reviewed. Besides, the feedback provided in the validation was used by the adapters to improve the face validity of the items.